IMPLEMENTASI MUSICAL LEARNING BERBASIS MULTISENSORIK DALAM PEMBELAJARAN MUFRODAT BAHASA ARAB ANAK USIA DINI - Ummidlatus Salamah; Najwa Salsa Bila; Chabibah Alamsyah (Prodi PGMI Institut Agama Islam Bani Fattah Jombang, 2026)
This study aims to describe the implementation of multisensory-based musical learning in Arabic vocabulary (mufrodat) learning for early childhood at RA Hidayatun Najah Tuban, analyze the implementation process of song media in increasing children's learning engagement, and identify its impact on children's Arabic vocabulary mastery. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving teachers and children aged 5-6 years. The learning process utilized the adapted “Pelangi-Pelangi” song combined with body movements, visual activities, and repetitive pronunciation to create an interactive and enjoyable learning atmosphere. The results showed that multisensory-based musical learning was implemented effectively through stages of planning, implementation, and evaluation integrated into Arabic learning activities. The use of song media increased students’ participation, enthusiasm, confidence, and learning motivation during the learning process. In addition, the implementation of multisensory-based musical learning positively impacted children’s ability to memorize, pronounce, and understand Arabic vocabulary more effectively. Therefore, this approach can serve as an innovative and meaningful learning strategy in Arabic language instruction for early childhood education.